Adsorption of Ni(II) Ion onto Calcined Eggshells: A Study of Equilibrium Adsorption Isotherm - Hans Kristianto; Novitri Daulay; Arenst Andreas Arie (Indonesian Journal of Chemistry, 2019)
Adsorption is one of the most effective and economical method to treat heavy metals in water. In this study, we utilize waste chicken eggshells as biosorbent to adsorb Ni(II). Furthermore we study the effect of eggshell calcination on its adsorption performance. The effect of calcination on the characteristic of eggshell was observed using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy (SEM-EDS). It could be observed that CaCO3 in eggshell was converted into CaO, and from SEM images the calcined eggshell became more porous than the uncalcined one. The effect of various parameters such as initial Ni(II) solution pH and initial Ni(II) concentration was investigated using batch adsorption experiments. The data obtained then fitted to Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich isotherms. The best pH for Ni(II) adsorption was found to be 6. From Langmuir and Dubinin-Radushkevich, it was found that calcined eggshells gave 60 times higher maximum adsorption capacity then uncalcined one. This increase was possible due to more porous structure of calcined eggshells. The adsorption process was found to be exothermic and physisorption. This result was confirmed by the decrease of % removal with increase of temperature. Furthermore, Langmuir isotherm was found to be the best model, indicating adsorption of Ni(II) was monolayer adsorption on homogenous surface.